Study of the patient positioning for a safer ultrasound guided upper cervical facet joints injection and third occipital nerve block - Studio del posizionamento del paziente per una più sicura procedura di blocco ecoguidato delle faccette cervicali superiori e del terzo nervo occipitale - Ezio Amorizzo; Fabrizio Micheli; Laura Patrizia Bucci; Felice Occhigrossi; Marco Mercieri (Publiediting, 2018)
Cervical facet joints injections and epidural injections are the two most common interventions in managing chronic cervical pain. The C2-C3 joint and the third occipital nerve are very dangerous targets to be injected due to the proximity of the vertebral artery in the last portion V3 from the transverse process of C2 to the foramen magno. This study demonstrates that the distance between the facet C2-C3 and vertebral artery increases of 90% by a 45 degrees head rotation. The position over mentioned seems to be more protective during the Third Occipital Nerve block and during the C2-C3 facet blockage because the vertebral and segmental arteries are shifted medially far and behind the articular pillar on coronal plane. The augmented distance is confirmed either by TC and ultrasound scan.